In-depth analysis of cystic fibrosis cases caused by CFTR gene variation and research on the prediction and simulation of the impact on protein function - Shan, Yuxia; Zhu, Ziwei; Liu, Xiaomei; Chi, Lei; Zhang, Jianqin; Cheng, Li; Liu, Tianyi (Frontiers in Pediatrics, 2025)
BackgroundCystic fibrosis (CF) is caused by CFTR gene mutations. Its diagnosis mainly depends on genetic and sweat chloride tests, but the complexity of these mutations challenges diagnosis.MethodsThis paper reports a new case of a Chinese child with cough and wheezing, suspected of having CF. Trio whole-exome sequencing for the pedigree was carried out to detect CFTR gene mutations. Five tools, namely Mutation Taster, PolyPhen-2, SIFT, FATHMM, and PROVEAN, were used to predict the impacts of mutations on protein function. AlphaFold was employed to predict protein structures, and GROMACS software was used to conduct stability analysis through molecular dynamics simulations.ResultsThe child was diagnosed with severe pneumonia, plastic bronchitis, and acute asthmatic bronchitis, with a high suspicion of CF. Whole-exome sequencing revealed compound missense mutations in the CFTR gene: c.1408 (exon 11) G>A (p.V470M) and c.650 (exon 6) A>G (p.E217G), both of which were homozygous mutations. Parental genetic tests showed that the father was heterozygous for the mutations, and the mother was heterozygous at the c.650 (exon 6) A>G locus and homozygous at the c.1408 (exon 11) G>A locus. The results obtained by different prediction tools varied, and molecular dynamics simulations indicated that these mutations significantly affected the stability of the CFTR protein.ConclusionAnalysis of this new case using multiple tools and computational chemistry simulations helps to further understand the impacts of mutations on CFTR protein function and the disease, offering novel insights into the diagnosis, treatment, and genetic counseling of CF caused by the complex and diverse mutations of the CFTR gene.